A lactate-related tSNE signature defines prognostic subtypes of bladder cancer and reveals LINC01094-mediated VIM stabilization in metastasis and drug resistance - Zhang, Pu; Zhang, Hegan; Yu, Wanli; Fan, Dage; Pan, Yao; Zhuang, Wei; Cai, Fangzhen; He, Qingliu (Frontiers in Immunology, 2025)
BackgroundBladder cancer (BLCA) is prone to metastasis and often shows poor responses to chemotherapy and immunotherapy. Investigating the underlying mechanisms of metastasis and drug resistance may therefore offer new therapeutic strategies for BLCA.MethodsPublicly available datasets were analyzed using consensus clustering and t-distributed stochastic neighbor embedding (tSNE) to characterize a lactate-related gene signature in BLCA. Gene set variation analysis (GSVA) was employed to assess signaling pathway activity, while immune cell infiltration in the tumor microenvironment (TME) was evaluated using single-sample gene set enrichment analysis (ssGSEA), the Estimation of Stromal and Immune cells in Malignant Tumors using Expression data (ESTIMATE), and CIBERSORT. RNA pull-down and RNA-binding protein immunoprecipitation (RIP) assays were then performed to confirm molecular interactions.ResultsTwo distinct BLCA subtypes were identified based on lactate-related gene expression, and a lactate-based tSNE score was constructed. This score demonstrated prognostic value and was integrated into a nomogram confirmed by a calibration curve. Functionally, higher tSNE scores correlated with immune- and inflammation-related pathways, as well as with immunotherapy efficacy in BLCA. Among candidate regulators identified, LINC01094 emerged as a key factor in BLCA metastasis and drug resistance. LINC01094 was predominantly localized in the cytoplasm and was upregulated in tumor tissues compared with adjacent normal tissues, acting as an unfavorable prognostic factor. In vitro, LINC01094 promoted metastasis and chemotherapy resistance, potentially by stabilizing VIM protein levels and inhibiting its ubiquitination.ConclusionsThis comprehensive analysis of lactate-related genes reveals how this gene signature may shape the tumor microenvironment and affect BLCA patient prognosis. Additionally, our data suggest that targeting LINC01094 with antisense oligonucleotides (ASOs) could reduce BLCA cell metastasis and enhance their sensitivity to chemotherapy.